Invastor logo
No products in cart
No products in cart

Ai Content Generator

Ai Picture

Tell Your Story

My profile picture
67505aae3df5935c2a9ae770

Compute the derivative of the function f(x) = 3x^3 - 2x^2 + x - 5

2 months ago
17

To compute the derivative of the function f(x) = 3x³ - 2x² + x - 5, we will apply the rules of differentiation. The derivative of a function gives us the rate at which the function's value changes as its input changes.

The differentiation rules we will use include:

  • Power Rule: If f(x) = x^n, then f'(x) = n * x^(n-1).
  • Constant Rule: The derivative of a constant is zero.
  • Sum Rule: The derivative of a sum of functions is the sum of their derivatives.

Now, let's differentiate each term of the function:

  1. Differentiate 3x³:
  2. Using the power rule, we have:

    • Derivative: 3 * 3x^(3-1) = 9x²
  3. Differentiate -2x²:
  4. Again, applying the power rule:

    • Derivative: -2 * 2x^(2-1) = -4x
  5. Differentiate x:
  6. The derivative of x (which is ) is simply:

    • Derivative: 1 * x^(1-1) = 1
  7. Differentiate -5:
  8. Since -5 is a constant:

    • Derivative: 0

Now, we can combine all the derivatives we calculated:

f'(x) = 9x² - 4x + 1 + 0

Thus, the derivative of the function f(x) is:

f'(x) = 9x² - 4x + 1

To illustrate how this derivative can be used, consider the following:

  • If we want to find the slope of the tangent line to the curve at a specific point, say x = 2, we can substitute x = 2 into the derivative:
  • f'(2) = 9(2)² - 4(2) + 1 = 9(4) - 8 + 1 = 36 - 8 + 1 = 29

  • This means that at the point where x = 2, the slope of the tangent line to the curve is 29.

In conclusion, the derivative of the function f(x) = 3x³ - 2x² + x - 5 is f'(x) = 9x² - 4x + 1. Understanding how to differentiate functions is essential in calculus and is widely applicable in various fields such as physics, engineering, and economics.

User Comments

Related Posts

    There are no more blogs to show

    © 2025 Invastor. All Rights Reserved